2021
DOI: 10.1038/s41598-021-92027-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gut microbiota in the acute phase after spinal cord injury correlate with severity of the lesion

Abstract: After spinal cord injury (SCI), patients face many physical and psychological issues including intestinal dysfunction and comorbidities, strongly affecting quality of life. The gut microbiota has recently been suggested to influence the course of the disease in these patients. However, to date only two studies have profiled the gut microbiota in SCI patients, months after a traumatic injury. Here we characterized the gut microbiota in a large Italian SCI population, within a short time from a not only traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…The overall quality of reverse reads was lower than that of forward reads for all the sequenced samples and, in this specific case, did not pass the quality filter in dada2 [ 50 ]. To overcome this issue, we applied an approach based on PE reads merging before denoising [ 51 , 52 ]. About 70% of input reads were successfully merged.…”
Section: Resultsmentioning
confidence: 99%
“…The overall quality of reverse reads was lower than that of forward reads for all the sequenced samples and, in this specific case, did not pass the quality filter in dada2 [ 50 ]. To overcome this issue, we applied an approach based on PE reads merging before denoising [ 51 , 52 ]. About 70% of input reads were successfully merged.…”
Section: Resultsmentioning
confidence: 99%
“…Another clinical study with 54 Turkish participants (41 SCI patients vs. 13 healthy controls) identified that butyrateproducing microbes of the Firmicutes phylum are significantly reduced in SCI patients than healthy controls (108). Recently, Bazzocchi et al investigated a large Italian SCI population acute phase after injury and age-and gender-matched healthy Italians (112). Their study revealed that the abundance of SCI patients' gut microbiota increased in potentially pathogenic, proinflammatory, and mucus-degrading bacteria and decreased in SCFAs producers.…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Since these groundbreaking studies, there has been an explosion of interest in how gut microbiota are altered after SCI, and how modulation of the gut microbiome might improve both neurological and immunological outcomes for SCI individuals [ 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. In regard to peripheral immunity, a recent study demonstrated that after a T9 contusive injury in mice, the gut microbiome displayed a reduced Firmicutes to Bacteroidetes phyla ratio as well as an increase in the phylum Proteobacteria that contains Gram-negative bacteria that produce the endotoxin LPS, which is associated with systemic inflammation [ 157 ].…”
Section: Potential Interventions To Improve Immunological Function Post-scimentioning
confidence: 99%